The Role of Darsak Platform in Developing Self-Learning Skills for a Sample of Ninth Grade Students in the Directorate of Education for the Second Zarqa District in Jordan - Tamerkan, Ferdoos Mohamad Mustafa (Journal of Educational and Psychological Sciences, 2022)
The current study aimed at identifying the level of the role of Darsak Platform in developing self-learning skills among a sample of ninth grade students in the Directorate of Education for the second Zarqa region in Jordan, and to determine whether there is a difference in the level of the role of Darsak Platform in developing self-learning skills for a sample of The ninth grade students in the Directorate of Education for the second Zarqa region between male and female students, and the descriptive analytical approach was used, where a questionnaire was developed to measure the extent to which students possess self-learning skills. and uploading it, taking responsibility and managing time, self-evaluation, and cooperating with others in the learning process, its validity and stability indications were verified. The study sample consisted of (321) male and female students who were chosen by random stratified method. the study concluded that the level of the role of Darsak platform in developing self-learning skills among a sample of ninth grade students in the Directorate of Education for the second Zarqa region was high with an arithmetic mean (3.68) WITH percentage (73.6%), and it came after (searching for information in and downloading it) in the first place in the first place with an arithmetic mean (3.78) a percentage (75.6%), followed by after (taking responsibility and time) in The second degree is an average promotion with a mean (3.70) and a percentage (74%), then came after (self-assessment) in the third degree an average promotion with a mean (3.66) and a percentage (73%), while after (teaching with others in the learning process) came first in the middle rank with its arithmetic mean (3.53) and a percentage (70.6%), and there are statistically significant differences in the level of the role of Darsak platform in developing self-learning skills due to gender and in favor of females. The study recommended the need to update Darsak platform and expand the presentation of educational materials on it, and for the Ministry of Education to provide the necessary equipment to use educational platforms in its schools to improve educational outcomes.